Uttar Pradesh lok sabha elections 2019: Modi's social engineering, development and smart politics - Verma, A.K. (Social Science In Perspective)
BJP$1 (Bs inclusive politics based on new social engineering, poor eccentric development schemes with focus on grassroots implementation and smart leadership by PM Narendra Modi won the BJP 2019 LS elections in UP. on the contrary. Congress$1 (Bs poor agenda, negative campaign and Rahul$1 (Bs non-serious leadership almost exterminated the party in the state. The SP-BSP gathbandhan ignored the fact that to succeed, a political coalition must be preceded by a social coalition that was not attempted by the gathbandhan constituents. After a very long, 2019 LS election in UP would be remembered as an election that defied caste and communal overtones and took a new trajectory of inclusion, development and leadership in Uttar Pradesh. - Reproduceds
Keywords: Elections - India, ModI, Narendra, - 1950, Prime ministers - India, India - Politics and government - 2014-